Intra- and inter-cycle velocity variations in sprint front crawl swimming - Fernandes, A.; Mezêncio, B.; Soares, S.; Carvalho, D. D.; Silva, A.; Vilas-Boas, J. P.; Fernandes, J. S. (Sports Biomechanics, 2022)
Intra- and inter-cycle velocity variations are of utmost importance for achieving enhanced swimming performances. However, intra-cycle events can impact and interfere with the subsequent cycles, making relevant to study several consecutive cycles allowing a better understanding of this possibility. We have assessed front crawl intra- and inter-cyclic velocity variations and overall biomechanical variables in sprint front crawl swimming. Twenty-seven elite swimmers performed 25 m all-out front crawl, were videotaped using moving cameras placed at the sagittal plane and were grouped according to their sprint mean velocity. Coefficient of variation, root mean square error and mean velocity differences between two consecutive paired cycles allowed assessing intra- and inter-cycle velocity variations. Visual inspection was performed to analyse possible variability causes and independent-measures t-test allowed comparing groups. Sprint front crawl was characterised by intra- (11.12 ± 2.98) and inter-cycle velocity variation (2.27 ± 0.80 of inter-cycle velocity coefficient of variation and 0.031 ± 0.014 of root mean square error), with no differences between fastest and slowest swimmers. Front crawl intra-cycle velocity variation was not related to mean velocity and cycle sequence but considered swimmers` personal strategy. Despite some abnormal oscillations within cycles, inter-cycle velocity variation was not caused by intra-cycle velocity variation, mean velocity or cycle sequence.